PERANCANGAN MEDIA PEMBELAJARAN FISIKA ANIMASI TIGA DIMENSI PADA MATERI INTI ATOM MENGGUNAKAN APLIKASI BLENDER UNTUK SEKOLAH MENENGAH ATAS - Prastowo, Rizo Budi; Nasir, Muhammad; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : Microscopic physics education subject like core atom is invisible physics subject that needed multimedia to help the students understanding the subject. All this time student understanding about this subject was still low and it make some of student afraid about this subject. Start from how important to understand this subject so we need to make the solution. Learning multimedia which base on three-dimensional animation that can create something abstract to be more real is the solution that given on this research. It was create by Blender application and designed by ADDIE design model that be based on pedagogic, program and learning subject. Result of this research is Blender application with 500 MB size that can be open by computer with processor dual core or equal and RAM 2GB as the minimum capacity. The validation data is 4,515 in very high category. It was found that is good to continue this research so that this learning multimedia can help students to understand about core atom subject.Keyword: Learning Multimedia, 3D Animation, Aplikasi Blender